Efektivitas Teknik Journaling terhadap Penurunan Stres Akademik pada Mahasiswa - Muhammad Alim; Ahmad Khaeroini; Muhammad Jamaluddin (Indonesian Journal Publisher, 2025)
This study tested the effectiveness of journal techniques (catharsis and gratitude) in reducing academic stress in college students. The method used was a quasi-experimental one-group pretest-posttest design, involving college students with above-average stress levels. The intervention was carried out for one week through three stages: (1) free writing for emotional expression, (2) gratitude journaling to build a positive perspective, and (3) independent daily journaling exercises. The results showed a significant decrease in academic stress levels after the intervention. The journal technique was proven to be effective as a simple, flexible, and independently adopted emotion regulation tool by college students to manage long-term academic stress. These findings support the use of writing-based interventions as an easily accessible and low-cost stress management strategy